2020
DOI: 10.1186/s13023-020-01634-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel gene variants in Polish patients with Leber congenital amaurosis (LCA)

Abstract: Background Leber congenital amaurosis (LCA) is a rare retinal disease that is the most frequent cause of congenital blindness in children and the most severe form of inherited retinal dystrophies. To date, 25 genes have been implicated in the pathogenesis of LCA. As gene therapy is becoming available, the identification of potential treatment candidates is crucial. The aim of the study was to report the molecular basis of Leber congenital amaurosis in 22 Polish families. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Hanein et al (2004) suggested a clinical flowchart according to which a child manifesting nystagmus, profound visual deficiency, and unrecordable ERG at birth or during the first months of life and developing photophobia, showing hypermetropia with a refractive error lower than +7, and VA better than FC, but worse than 1/20, will probably have RPGRIP1 or AIPL1 mutations. While this flowchart holds true for many of the 228 RPGRIP1 patients included in the present analysis (from multiple centers and publications), not all patients with RPGRIP1 causative mutations have nystagmus from birth (156 patients, which are 68%), a minority still have recordable ERG responses even after the age of 10 years, approximately 25% of patients are nyctalopic, 20% (25/124, 7 of them had NLP) of patients had VA lower than FC (Dryja et al, 2001;Galvin et al, 2005;McKibbin et al, 2010;Walia et al, 2010;Chen et al, 2013;Fakhratova, 2013;Huang et al, 2013Huang et al, , 2017Khan et al, 2013Khan et al, , 2014Wang et al, 2016;Han et al, 2017;Jinda et al, 2017;Hosono et al, 2018;Weisschuh et al, 2018;Avela et al, 2019;Jamshidi et al, 2019;Sallum et al, 2020;Skorczyk-Werner et al, 2020), and 25% (32/124) had a VA better than 1/20 (McKibbin et al, 2010;Fakhratova, 2013;Suzuki et al, 2014;Saqib et al, 2015;Han et al, 2017;Huang et al, 2017;Birtel et al, 2018;Weisschuh et al, 2018;Imani et al, 2018;Miyamichi et al, 2019;Skorczyk-Werner et al, 2020;Sallum et al, 2020;Sato et al, 2020). In addition, there are p...…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hanein et al (2004) suggested a clinical flowchart according to which a child manifesting nystagmus, profound visual deficiency, and unrecordable ERG at birth or during the first months of life and developing photophobia, showing hypermetropia with a refractive error lower than +7, and VA better than FC, but worse than 1/20, will probably have RPGRIP1 or AIPL1 mutations. While this flowchart holds true for many of the 228 RPGRIP1 patients included in the present analysis (from multiple centers and publications), not all patients with RPGRIP1 causative mutations have nystagmus from birth (156 patients, which are 68%), a minority still have recordable ERG responses even after the age of 10 years, approximately 25% of patients are nyctalopic, 20% (25/124, 7 of them had NLP) of patients had VA lower than FC (Dryja et al, 2001;Galvin et al, 2005;McKibbin et al, 2010;Walia et al, 2010;Chen et al, 2013;Fakhratova, 2013;Huang et al, 2013Huang et al, , 2017Khan et al, 2013Khan et al, , 2014Wang et al, 2016;Han et al, 2017;Jinda et al, 2017;Hosono et al, 2018;Weisschuh et al, 2018;Avela et al, 2019;Jamshidi et al, 2019;Sallum et al, 2020;Skorczyk-Werner et al, 2020), and 25% (32/124) had a VA better than 1/20 (McKibbin et al, 2010;Fakhratova, 2013;Suzuki et al, 2014;Saqib et al, 2015;Han et al, 2017;Huang et al, 2017;Birtel et al, 2018;Weisschuh et al, 2018;Imani et al, 2018;Miyamichi et al, 2019;Skorczyk-Werner et al, 2020;Sallum et al, 2020;Sato et al, 2020). In addition, there are p...…”
Section: Discussionmentioning
confidence: 94%
“…For example, nystagmus and oculodigital signs do not appear in all patients. While most of the patients are hyperopic (Dryja et al, 2001;Galvin et al, 2005;Fakhratova, 2013;Khan et al, 2013Khan et al, , 2014Verma et al, 2013;Suzuki et al, 2014;Wang et al, 2016;Han et al, 2017;Huang et al, 2017;Sato et al, 2020), some myopic patients were identified (Tiwari et al, 2016;Imani et al, 2018); most of the patients reported light aversion (McKibbin et al, 2010;Fakhratova, 2013;Huang et al, 2013;Khan et al, 2013Khan et al, , 2014Suzuki et al, 2014;Saqib et al, 2015;Wang et al, 2016;Sato et al, 2020;Skorczyk-Werner et al, 2020), but some emphasize nyctalopia as a major visual symptom (McKibbin et al, 2010;Birtel et al, 2018;Miyamichi et al, 2019). Hanein et al (2004) suggested a clinical flowchart according to which a child manifesting nystagmus, profound visual deficiency, and unrecordable ERG at birth or during the first months of life and developing photophobia, showing hypermetropia with a refractive error lower than +7, and VA better than FC, but worse than 1/20, will probably have RPGRIP1 or AIPL1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of these changes are variants that impact on splicing despite being distal to the intron-exon junction (like the TRPM1 c.965 + 29G>A change found in a participant of this study). Such sequence alterations have been reported in a number of genes associated with retinal diseases including ABCA4, USH2A, CACNA1F, CEP290, GUCY2D and RPE65 (den Hollander et al 2006;Liquori et al 2016;Sangermano et al 2019;Zeitz et al 2019;Skorczyk-Werner et al 2020). Identifying such changes is particularly important as there are implications for therapeutic development, given that this group of variants has been shown to be Fig.…”
Section: Discussionmentioning
confidence: 96%
“…2019; Skorczyk‐Werner et al. 2020). Identifying such changes is particularly important as there are implications for therapeutic development, given that this group of variants has been shown to be amenable to anti‐sense oligonucleotide and CRISPR‐Cas9 approaches (Garanto et al.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of RPE65associated LCA varied considerably in various countries, from 1.26% up to 95% in clinically diagnosed patients [2, and from 3.95% to 40% among those with a molecular diagnosis of IRD [2,25,27,37,[42][43][44][45][46]. The proportion of RPE65 gene mutations in LCA families worldwide was estimated at 6.15% [47], but the percentages of the mutation-carrying families from various countries differed substantially, from 1% to 18.18% in clinically diagnosed cases [48][49][50][51][52] and from 7.14% to 13.64% in molecularly diagnosed ones [2,53,54] (Table 1). The prevalence of RP worldwide was reported at 11.09 to 47.62 per 100,000 [5,[55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Epidemiology Of Rpe65-associated Retinal Dystrophymentioning
confidence: 99%